Successful management of fetal mummification in non-descript buffalo heifer by medical termination and episiotomy operation - Manokaran, Sakthivelu; Selvaraju, Mani; Palanisamy, Mahakrishnan; Prakash, Subramanian (Buffalo Bulletin, 2024)
A 9-month pregnant non-descript buffalo heifer was presented with the history of vaginal discharge. The case was diagnosed as fetal mummification during clinical and ultrasound examination. The parturition was induced with PGF2α. The animal was not responded to and hence the second dose of PGF2α was given 72 h later. The cervix was fully dilated forty-eight hours after second PGF2α injection but due to vulval constriction it was unable to deliver the fetus. Hence an episiotomy was performed and the mummified fetus was delivered.